Why economists disagree : an introduction to the alternative schools of thought (Albany : State University of New York Press, 1998)
Austrian economics and the market process. Post-Keynesian economics for an uncertain world. Beyond the market: social and institutional economics. The changing face of radical political economy. Where do we go from here? New philosophical issues.
Keywords: Economics; Economics; Economics -- History; Economics -- Philosophy